PENELITIAN TINDAKAN KELAS SEBAGAI USAHA PEMECAHAN MASALAH DALAM PEMBELAJARAN PENDIDIKAN JASMANI - Ahmad Rithaudin (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2006)
Classroom action research is one of the efforts in solving problems faced by teachers duringtheir learning process. The learning process covers physical education learning in classesas well as practices in laboratory and field. Teachers hold an important role in implementingclassroom action research. Teachers are aware of the issues faced by students in class. Inphysical education, the motoric ability of students varies. Teachers are responsible in planning,acting, doing, observing and reflecting. Teachers can also be assisted by a partner or anexpert. Two important factors in classroom action research especially in physical educationare the usage of teaching media and teaching styles.Keywords: classroom action research, problem solving, physical education teaching andlearning.